Preparation of Antheraea pernyi Silk Fibroin Microparticles through a Facile Electrospinning Method - Xiufang Li; Qiang Zhang; Yanfei Feng; Shuqin Yan; Jing Qu; Renchuan You (Advances in Materials Science and Engineering)
The goal of this study was to fabricate Antheraea pernyi silk fibroin (ASF) microparticles using electrospinning under mild processing conditions. To improve processability of the ASF solution, poly(ethylene oxide) (PEO) was used to regulate viscosity of ASF solution for electrospinning. It was found that the blend of ASF with PEO could form a bead-on-string structure with well spherical particles. Furthermore, aqueous ethanol and ultrasonic treatments could disrupt the nanofibrillar string structure between particles and ultimately produced water-insoluble ASF particles with submicron scale. Cell viability studies indicated that the ASF microparticles were nontoxic to EA926 cells. Moreover, fluorescent images based on FITC labeling showed that the ASF microparticles were easily uptaken by the cells. Aqueous-based electrospinning provides a potentially useful option for the fabrication of ASF microparticles based on this unique fibrous protein.